CircCCDC66: Emerging roles and potential clinical values in malignant tumors - Wang, Xiaoxiao; Zhang, Chao; Song, Huangqin; Yuan, Junlong; Zhang, Lei; He, Jiefeng (Frontiers in Oncology, 2023)
Circular RNAs (circRNAs) are endogenous noncoding RNAs (ncRNAs) with closed-loop structures. In recent years, it has become the latest research hotspot in the field of RNA. circCCDC66 was identified as a novel oncogenic circRNA, and it was upregulated in various malignancies including thyroid cancer, non-small cell carcinoma, gastric cancer, colorectal cancer, renal cancer, cervical cancer, glioma, osteosarcoma, and so on. It is worth noting that circCCDC66 mediates cancer progression by regulating epigenetic modifications, alternative splicing, transcription, and protein translation. The oncogenicity of circCCDC66 mainly inhibits or promotes the expression of related genes through direct or indirect pathways. This suggests that circCCDC66 is a novel biomarker for cancer diagnosis, prognosis assessment, and treatment. It holds promise as a potential target for designing novel tumor therapeutic interventions. However, there is currently no review on the relationship between circCCDC66 and cancer. Therefore, this article reviews the latest research progress on the expression, biological function, and regulatory mechanism of circCCDC66 in various malignant tumors. This could provide insights for exploring new strategies for early diagnosis and targeted therapy of malignancies.